PERSEPSISUKUDAYAKKALISTERHADAPKEARIFANLOKAL SIPAUTANGDIDESARANTAUKALISKABUPATEN KAPUASHULU - Kristina Subek; Yohanes Bahari; Stella Prancisca (Universitas Tanjungpura, 2021)
AbstractThis article is entitled